Dentro i confini simbolici del gender order nel volontariato: pratiche e narrazioni della partecipazione delle donne - Milani, Stella (SocietàMutamentoPolitica, 2021)
Over the last two decades several sociological contributions have gradually shown a new interest in gender analysis of volunteering. Available statistical data indicate that this field of participation, although crossed by complex and contrasting dynamics, tends to strongly replicate the symbolic boundaries of gender order. Thus, we observe a structural gender-based division of tasks and power’s roles that men and women play within organizations. The conceptual overlapping between voluntary (unpaid) work and care that can occur in women’s volunteering stimulates to explore the symbolic foundations of these gender inequalities. The purpose of this article is to investigate the social construction of gender through the women’s ways of “doing” and “conceiving” voluntary work, focusing on variable articulations of ontological complicity between structures of male domination and women volunteer’s habitus. Using a qualitative approach, volunteer women’s narratives are analysed to examine the links between conceptions of volunteering, meanings of care and perspectives on gendered leadership in voluntary organizations. The findings of this exploratory analysis, showing different sets of meanings related to the experience of women’s volunteering, suggest to further investigate the links between styles of volunteering (collectives and reflexives) and practices by which gender is created and recreated through social participation.